Simulation on the influence of the shape of the carabiner as a hanging accessory on stress distribution using Autodesk Fusion 360 - Muhammad Rizki; Adhes Gamayel; Mohamad Zaenudin (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
Engineering and innovation in the manufacturing process will continue to be carried out. This aims to ensure that there are always improvements in every product made, both in terms of design, materials used, and how the production process is carried out. Product design innovation is often also aimed at efficiency and reducing product production costs. Innovation in a product must be to improve, not reduce the value and usefulness of the product being made. The aim of this research is to determine the distribution of stress and strain as well as the safety factor of carabiners as hanging accessories using polypropylene polymer material. The research uses experimental methods, namely observing the simulation results that occur in the form of stress, strain and safety factors, as well as knowing the cause and effect phenomena that occur in the design of a carabiner for an accessory. By changing the shape of each design to the upper end of the frame in the direction of the carabiner gate, R15, R30 and R45. As well as varying the load given by 10 N to 100 N, with an increase in force of 10 N in each simulation carried out, with axial and vertical loading directions. By ignoring the type of gate and the shape of the connection on the carabiner gate. The different shapes in each carabiner design cause differences in the tension distribution that occurs. The R15 design has a maximum stress value at a load of 100 N, namely 25.03 MPa, the R30 design is 33.78 MPa, and the R45 design is 63.61 MPa. The vertical loading direction achieves a good safety level of 4.0 at a load of 20 N in the R15 and R30 designs. Meanwhile, axial loading does not achieve product safety targets. The difference in calculating the factor of safety is 4.0 between the results of computer computing and the results of analytical calculations using a formula, namely 1% of the maximum limit of 5%.